Human Antihemophilic Factor (AHF) Purification A Comparison of Two Procedures - Hurt, J. P; Wagner, R. H; Brinkhous, K. M (Thrombosis and Haemostasis, 1966)
A method is described for the precipitation from plasma of a human AHF fraction (Fraction AA) with beta alanine. The Fraction AA is further purified by reprecipitation with beta alanine or by adsorption with Florigel or bentonite. Reprecipitation with beta alanine is a convenient step as no additional equipment or reagents are required for the second precipitation. All reagents can be rendered sterile and free of pyrogens. When the precipitates are quantitatively dissolved, the yields are greater than 70% and purification ranges from 300-600 times. The adsorption procedure also has advantages. Adsorption adds only 45 minutes to a 6 hour fractionation. AHF recovery is as high as 70% with a purification of 3,000 to 5,000 times.